Neuroprotective Properties of Fermented Malted Rice Obtained Under Different Processing Conditions - Albarracín, Micaela (2025)
Two products fermented with lactic acid bacteria (LAB) were obtained using malted rice (FR)and mashed malted rice (FMR). Peptide, phenolic acids, and γ-aminobutyric acid (GABA)contents and neuroprotective activities were evaluated before and after simulated gastrointestinaldigestion. GABA contents of fermented products were 45 and 51 mg 100 g−1, witha bioaccessibility of 51 and 45% for FR and FMR, respectively. Both fermented malted riceproducts exhibited inhibitory effects against tyrosinase, acetylcholinesterase, and prolyloligopeptidase, with FR demonstrating the highest inhibitory activity. The neuroprotectiveproperties were increased after digestion and could potentially be attributed to bioactivepeptides generated by germination, fermentation, and digestion, as well as free phenolicacids. These findings suggest that fermented malted rice possesses promising biofunctionalproperties and may serve as suitable dietary options for individuals with gluten and lactoseintolerance, offering additional neuroprotective benefits.